PERANCANGAN SISTEM STOK BARANG BERBASIS WEB PADA ASOSIASI PENYELENGGARA JASA INTERNET INDONESIA MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Arif Nurdiyan Syah Putra Utama; Alfat Ardiansa; Muhamad Wildan Fadlizar; Saprudin (Journal of Research and Publication Innovation, 2025)
This research was conducted as one of the academic requirements to complete studies. This research activity aims to design an efficient web-based inventory system for the Association of Indonesian Internet Service Providers (APJII) using the Rapid Application Development (RAD) method. This system is designed to help manage inventory processes more efficiently, accurately, and in a computerized manner compared to manual systems or previously unintegrated processes. The application was developed using a suitable web programming language (e.g., PHP/JavaScript/Python) with a UML (Unified Modeling Language) approach, including use case diagrams, activity diagrams, sequence diagrams, and ERD (Entity Relationship Diagrams), and utilizing the MySQL database for data storage. During the implementation of the research, the author conducted an analysis of user needs through direct interviews with related parties at APJII, designing the application interface, creating a database, and implementing features such as recording incoming and outgoing goods, managing item data, stock reporting, and other inventory-related features. After going through the functionality testing stage, the system was proven to be able to replace inefficient and error-prone inventory management processes, as well as providing easy and secure data access through a web platform. The final result shows that the created system is able to improve the efficiency of inventory management processes, minimize the risk of data loss or error, and provide an integrated digital solution for APJII.